The Influence of Brand Satisfaction, Customer Engagement, Innovativeness, Social Media Marketing to Purchase Intention through Brand Loyalty in Kampung Keren Kediri City: - - Diana Ambarwati; Rike Selviasari; Dewi Wungkus; Anisak Salsabila (International Journal of Economics, Business and Innovation Research, 2025)
The recent surge in tourist visits in 2024 to Kediri City, marked by 31.37% increase over last year, indicates heightened activity among domestic and international travelers. This growth is attributed to innovative services, enhancing visitor satisfaction through unique experiences. Additionally, effective social media marketing strategies contribute to increased visitor awareness and interest by providing relevant and engaging information. This study aims to assess the Kampung Keren program based on brand loyalty, purchase intention, customer engagement, service innovativeness, and the role of social media marketing in promoting these aspects. The study involves 42 respondent utilizing Instagram for their tourism promotions. Purposive sampling was employed, and data collection occurred via questionnaires distributed during September and October 2024. The data was analyzed using SmartPLS, combining both primary and secondary sources. The results of this research indicate that there is a positive and significant direct relationship between innovativeness on customer engagement, brand loyalty on purchase intention. There is negative and significant direct relationship between customer engagement on brand loyalty. Insignificant direct relationship between customer engagement on brand satisfaction, brand satisfaction, innovativeness and social media marketing on brand loyalty, social media marketing on purchase intention. There is a negative and significant indirect relationship between customer engagement on brand loyalty mediated by brand satisfaction. There is an insignificant indirect relationship between innovativeness on brand satisfaction mediated by customer engagement, customer engagement and innovativeness on brand loyalty mediated by brand satisfaction and customer engagement, brand satisfaction, innovativeness and social media marketing on purchase intention mediated by brand loyalty.